2012
DOI: 10.1111/aos.12015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 23‐gauge sutureless sclerotomy architecture and clinical outcomes in macular and non‐macular surgery using spectral‐domain optical coherence tomography

Abstract: In 23-G PPV, non-macular surgery is associated with a significant postoperative IOP decrease in comparison with macular surgery, which could be explained by the most remodelled wound architecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…Increased surgical manipulation and repeated passage of instruments through superior sclerotomies have been related to increased suturing at these sclerotomies when compared to the relatively static infusion port. [ 2 18 ] In our study, the proportion of sutured sclerotomies in SNQ and INQ was significantly less than self-sealed sclerotomies, whereas the proportion of self-sealed and sutured sclerotomies was not statistically different in STQ. When analyzing the port sites in relation to the right-handed surgeon, we found that left-sided ports and infusion ports had proportionally lesser suturing, whereas the right-sided ports were sutured more often.…”
Section: Discussioncontrasting
confidence: 43%
See 4 more Smart Citations
“…Increased surgical manipulation and repeated passage of instruments through superior sclerotomies have been related to increased suturing at these sclerotomies when compared to the relatively static infusion port. [ 2 18 ] In our study, the proportion of sutured sclerotomies in SNQ and INQ was significantly less than self-sealed sclerotomies, whereas the proportion of self-sealed and sutured sclerotomies was not statistically different in STQ. When analyzing the port sites in relation to the right-handed surgeon, we found that left-sided ports and infusion ports had proportionally lesser suturing, whereas the right-sided ports were sutured more often.…”
Section: Discussioncontrasting
confidence: 43%
“…On the other hand, analysis of the influence of surgery duration on sclerotomy closure has shown conflicting results. [ 2 3 16 18 ] In our cohort, when comparing the time taken for surgeries that required suturing and those that did not, we found no significant difference. This could be explained by the wide surgical indications for patients in both groups of this study.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations